Development of effective lead removal from wastewater by graphene oxide - Nik Abdul Ghani, Nik Rashida; Jami, Mohammed Saedi; Alam, Md. Zahangir; Wan Salim, Wan Wardatul Amani (2019)
This study aims to remove lead from wastewater effluent by adsorption process using graphene oxide (GO). FTIR revealed the presence of functional groups such as carboxyl, epoxy, and hydroxyl. The morphology of GO was analysed by SEM displayed GO consists of randomly aggregated and crumpled structure, showed some wrinkle and fold area on the surface of GO which confirmed that the graphite was well exfoliated during the oxidation process. The adsorption parameters were optimized using fractional factorial design. GO demonstrated 99.98 % of lead removal at initial concentration of 100 mg/L lead, pH 9 and 60 min of contact time. Adsorption studies indicated that the adsorption fitted well with the Langmuir isotherm model, predicted the monolayer coverage removal of lead.